dSIR2 and dHDAC6: two novel, inhibitor-resistant deacetylases in Drosophila melanogaster. - Barlow, A.L.; van Drunen, C.M.; Johnson, C.A.; Tweedie, S.; Bird, A.; Turner, B.M. (Experimental Cell Research, 2001)
We have identified new members of the histone deacetylase enzyme family in Drosophila melanogaster. dHDAC6 is a class II deacetylase with two active sites, and dSIR2 is an NAD-dependent histone deacetylase. These proteins, together with two class I histone deacetylases, dHDAC1 and dHDAC3, have been expressed and characterized as epitope-tagged recombinant proteins in Schneider SL2 cells. All these proteins have in vitro deacetylase activity and are able to deacetylate core histone H4 at all four acetylatable lysine residues (5, 8, 12, and 16). Recombinant dHDAC6 and dSIR2 are both insensitive to TSA and HC toxin and resistant, relative to dHDAC1 and dHDAC3, to inhibition by sodium butyrate. Indirect immunofluorescence microscopy of stably transfected SL2 lines reveals that dHDAC1 and dSIR2 are nuclear, dHDAC6 is cytosolic, and dHDAC3 is detectable in both cytosol and nucleus. dHDAC6 and dSIR2 elute from Superose 6 columns with apparent molecular weights of 90 and 200 kDa, respectively. In contrast, dHDAC1 and dHDAC3elute at 800 and 700 kDa, respectively, suggesting that they are components of multiprotein complexes. Consistent with this, recombinant dHDAC1 coimmunoprecipitates with components of the Drosophila NuRD complex and dHDAC3 with an as yet unknown 45-kDa protein.